Antioxidant Properties, α-Amylase and α-Glucosidase Inhibitory Activities of Maesobotrya barteri Leaves Extracts in Rats - Enin, Godwin Ndarake; Ita, Basil Nse; Thomas, Paul Sunday; Okokon, Jude Efiom; Lawson, Blessing Ofonime; Ohanaka, Chidera Getrude (Sciences of Pharmacy, 2025)
Maesobotrya barteri is widely used in Nigerian ethnomedicine to treat diabetes, arthritis, and infections. In this study, the methanol and aqueous leaf extracts' phytochemical constituents and antioxidant potentials were evaluated using standard procedures. At the same time, the enzyme inhibitory activity of methanol extract on α-amylase and α-glucosidase in rats was also investigated. The antioxidant properties of the extracts were evaluated by the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity and ferric reducing power (FRAP). Phytochemical screening of methanol and aqueous extracts revealed the presence of flavonoids, alkaloids, saponins, tannins, and cardiac glycosides. Total phenolics and flavonoids of the extracts ranged from 0.04 to 3.18 mg of GAE/g and from 27.70 to 57.70 mg of QE/g, respectively. Antioxidant analysis showed IC50 values of DPPH (192.95, 196.04, and 17.19 µg/mL) and FRAP (30.48, 37.64, and 38.15 µg/mL) for the methanolic extract, aqueous extract, and ascorbic acid, respectively. Assessment of the methanolic extract against α-amylase and α-glucosidase enzymes in rats at doses of 150, 300, and 450 mg/kg using starch, sucrose, and maltose as substrates, with acarbose as a reference drug, significantly reduced blood glucose levels (p < 0.05). These findings suggest that M. barteri leaf extract has antioxidant properties and inhibits both α-amylase and α-glucosidase enzymes in rats, likely due to the phytochemicals present in the extract.